An Investigation of Teaching Aids Used by English Teachers in Teaching Vocabulary for Young Learners - Sanjaya, I Gede Heri; Dewi, Ni Luh Putu Eka Sulistia; Paramartha, Anak Agung Gede Yudha (Journal of Educational Study, 2022)
This qualitative study aims at investigating the teaching aids used to teach vocabulary for young learners. The data were collected using questionnaires and interview to determine the kinds of teaching aids used to teach vocabulary, the challenges in implementing them, and how English teachers face these challenges. The data collected were analyzed qualitatively by referring to Miles & Huberman (1994). The results show that the dominant type of teaching aids used by the English teachers to teach English to the young learners is audio-visual which is a combination of visual and audio aids was seldomly used by the teachers. According to the interview, the teachers felt that students were more engaged by visuals and audiovisuals because teachers can place interesting decorations to guide the students; for example, a student's favorite cartoon character or animal. The result of the interview also showed that the teachers found challenges in implementing the teaching aids, namely (a) time consuming (b) quality of teaching aids (c) technical difficulties. To face the challenges, teachers usually consider alternatives that are equivalent to the media that should have been used, allocated time, and also skills in operating electronic to implement the teaching aids.